Cultural lag and visionary challenges: Speculative approach to generative design - Weng, Wei (Вестник Томского государственного университета. Культурология и искусствоведение)
This paper presented an attempt to formulate Speculative Generative Design (SGD) approach (Generative Design based on “Speculative Design” Theory) to contemporary design methodology. We suppose that generative art and design – rooted in Modernist tradition of creative practices and currently developed as computer Artificial Intelligence based technology – should be integrated with speculative design as the critical intellectual synthesis and design methodology in the context of rapid social change and so called “cultural lag” (W. Ogburn). In authors’s perspective SGD can productively use advantages of technological and cultural determinist theoretical frameworks and stimulate creative potential of uncertainties implicit to technological driven design. Computer algorithms and programming languages could change the necessity of the designer imperative. For many practitioners these changes also open a new area of interdisciplinary intersections and collaborations between arts, design and technology. As it was demonstrated in recent publications, origins of generative art and design come from modernist visionary art and have more than century of very rich history. Authors apply the philosophy of speculative design as a framework to investigate the experimental future of generative design, based on computer algorithmic methods. Fundamental explanations of speculative approach we use presented in the book by Dunne and Raby “Speculative everything. Design, Fiction, and Social Dreaming”. Following this in order to help designers effectively explore generative design and improve their design decisions, we offer an SGD (Generative Design based on “Speculative Design” Theory) design methodology. Currently different cultures and ideologies are cognizant of the distinctions between the original settings and their own national contexts since speculative design is a culturally dimensional design methodology framework. From the bigger theoretical perspective contradictions between technological and cultural determinism could be solved in our approach in speculative manner through the generative design prototyping with the focus on possible deviations not functional capacities. With SGD-prototyping we transfer the problem into the virtual world and parallel designs appearing for creative transformations. Using props from science fiction novels and film and television dramas as media, and based on virtual future scenes and corresponding science fiction-like writing structures, future design becomes an innovative framework logic.